Effects of Fibroblast-Myocyte Coupling on Cardiac Conduction and Vulnerability to Reentry: A Computational Study - Xie, Yuanfang (2009)
BACKGROUND: Recent experimental studies documented that functional gap junctions form between fibroblasts and myocytes, raising the possibility that fibroblasts play roles in cardiac electrophysiology that extend beyond acting as passive electrical insulators. OBJECTIVES: Using computational models, we investigated how fibroblasts may affect cardiac conduction and vulnerability to reentry under different fibroblast-myocyte coupling conditions and tissue structures. METHODS: Computational models of two-dimensional tissue with fibroblast-myocyte coupling were developed and numerically simulated. Myocytes were modeled by the Phase I of the Luo-Rudy model and fibroblasts by a passive model. RESULTS: Besides slowing conduction by cardiomyocyte decoupling and electrotonic loading, fibroblast coupling to myocytes elevates myocyte resting membrane potential, causing conduction velocity to first increase and then decrease as fibroblast content increases, until conduction failure occurs. Fibroblast-myocyte coupling can also enhance conduction by connecting uncoupled myocytes. These competing effects of fibroblasts on conduction give rise to different conduction patterns under different fibroblast-myocyte coupling conditions and tissue structures. Elevation of myocyte resting potential due to fibroblast-myocyte coupling slows sodium channel recovery, which extends post-repolarization refractoriness. Due to this prolongation of myocyte refractory period, reentry was more readily induced by a premature stimulation in heterogeneous tissue models when fibroblasts were electrotonically coupled to myocytes compared to uncoupled fibroblasts acting as pure passive electrical insulators. CONCLUSIONS: Fibroblasts affect cardiac conduction acting as obstacles, or by creating electrotonic loading and elevating myocyte resting potential. Functional fibroblast-myocyte coupling prolongs myocyte refractory period which may facilitate induction of reentry in cardiac tissue with fibrosis.